April fool's rules! - Katschke, Judy.; Copyright Paperback Collection (Library of Congress) (New York : HarperEntertainment, 2002)
Mary-Kate has a starring role in the school play, but when her twin sister Ashley finds out that Mary-Kate's role involves kissing Ashley's big crush, Ross Lambert, she's determined to find a way to prevent it.
"A Parachute Press book."
"Based on the TV series"-- Cover.
Keywords: Twins; Sisters; Acting